PENTINGNYA PENDIDIKAN LINGKUNGAN HIDUP BAGI ANAK USIA DINI - Siti Rabiatul Adawiyah (Musawa: Journal for Gender Studies, 2022)
Environmental problems are not only related to the symptoms of evolutionary natural change, but also to the pollution caused by industrial and family waste. Therefore, environmental education for early childhood is expected to be one of the patterns to manage and protect the environment around us. models that can be used Conservation Scout model is used as a means to provide education on environmental awareness and concern. introduction to the environment for early childhood, the environment consisting of human resources, biological natural resources, non-biological natural resources, and artificial resources and elements of the natural environment, both physical and biological.